Methodological Quality and Characteristics of the Undergraduate Psychology Theses of a Private University of Peru - Mamani Benito, Oscar Javier (2018)
The objective was to determine the methodological quality and identify the characteristics of the psychology theses approved in the 2014-2017 period of a private university in Peru. The study is descriptive and bibliometric, in which the study population was 161 theses approved in the period 2014 - 2017, out of which 149 extensive files available in the institutional repository were analyzed. The grading format of the final report of research works created at the National University of Trujillo was used as an instrument. The main results indicate that 72.5% of the theses were carried out by two authors, 81.2% correspond to the correlation type, 66.4% were focused on the clinical and health psychology research line, 47% involved the school population, mostly adolescents (69.1%) and only 6% of the works were published. On the other hand, regarding the methodological quality, it was found that the majority of the theses (83) showed good quality, and with respect to their components, low scores were found in background (.57), sample size (.58), statistical analysis (. 43), contrast design (.49) and discussion (.53). It is concluded that the theses defended in the 2014- 2017 period are characterized by being of non-experimental design, mostly their school study population is adolescents and maintain a quality between regular and good, showing methodological deficiencies in the statistical management.